Anomalous packing state in Ce-Ga-Cu bulk metallic glasses - Zhao, Y.; Li, D.D.; Qu, B.Y.; Zhou, R.L.; Zhang, B.; Sato, K. (Intermetallics, 2017)
Formation mechanism of bulk metallic glasses (BMGs) with high glass-forming ability (GFA) has been a long-standing subject in the field of solid state physics. To highlight the GFA-associated local atomic structure, element-specific positron annihilation spectroscopy was conducted for recently discovered ternary Ce70GaxCu30-x (x = 6–13; at.%) BMGs. We succeeded in identifying the packing structure under the condition of ambient pressure, in which Ce atoms are concentrated more than that in Ce crystal. This anomalous glassy state is most efficiently formed at the Ga concentration of ∼10%, where the best glass-forming ability (GFA) is experimentally observed. First-principles computer simulation results suggest that this anomalous packing structure is associated with Ce-4f electron delocalization in the Ce-Ga-Cu BMGs. The findings provide unambiguous evidence for the relationship between the packing-efficient local structure and the GFA. •Positron annihilation revealed an anomalous packing state in CeGaCu bulk metallic glasses.•This anomalous glassy state is most efficiently formed at the best glass forming composition macroscopically observable.•The findings indicate that the locally-concentrated atomic structure is crucial for formation of bulk metallic glasses.